S11 parameter results comparison in reconfigurable antennas under simulation and measurement - V. Reji; C. T. Manimegalai (Institute of Advanced Engineering and Science, 2023)
In this paper, a simulation and measurement return loss parameter results comparison in frequency reconfigurable antenna is proposed. More lowprofile and compact microstrip antennas have been developed in recent years for 5 GHz, 5G, WLAN, Wi-Fi, and ISM band applications. These antenna frequency bands may be single, dual, or multiband. The small microstrip antenna, without connecting any external devices like switches, resonators, and passive elements, does not show any variations in their simulation and measurement results like return loss (S11 parameter), gain, and efficiency. However, in the S11 parameter most frequency reconfigurable antennas show a mismatch between simulation and measurement results. The reason for this mismatch between the simulation and measurement results are given in the paper.